STITCH-256: A dedicated cryptographic hash function - Jamil N.; Mahmod R.; Z'aba M.R.; Udzir N.I.; Zukarnain Z.A. (2023)
Hash functions are an impodant cryptographc primitive in a wide range of applicatiom, such as message authentication and digital signatures. Among others, Message Digest (MD)-415, Secure Hashing Algorithm (SHA)-OI1R and RACE Integrity Primitives Evaluation Message Digest (RIPEMD) family are examples of widely used hash functiom in cryptographic applicatiom. However with the advances of cryptanalysis, MD-415, SHA-011 andRIPEMD were broken in 2004-2005 after more than a decade of use. Since then, the structure and components of cryptographc hash functiom have been studied and revisited extensively by the cryptographic community. This study describes a 256-bit hash functionnamed as STITCH- 256, to overcome problems found inMD- and SHA-family hash functions. We analyze all the components of STITCH-256 andthe security analysis of STITCH-256 shows that it is not feasible to comtruct a collision path for STITCH-256 with a high probability of success. 2012 Asian Network for Scientific Information.